Prof. Il-Hoi Kim: a tribute - Huys, Rony (Zootaxa, 2016)
Prof. Il-Hoi Kim was born during the Korean War on 28 February 1952 in Buan, North Jeolla Province (South Korea), near the coast of the Yellow Sea whose tidal flats would become one of his favourite sampling grounds during his scientific career. From an early age he developed an intense interest in natural history in general and marine biology in particular. He obtained his B.Sc. in 1974 at the Department of Biology Education, Gongju National College of Education. Between 1974 and 1976 he was conscripted into the South Korean military during which he progressed to the rank of lieutenant of artillery in the Reserve Officers’ Training Corps (ROTC). After his graduation in 1980 at the Department of Zoology, Seoul National University, Il-Hoi Kim moved to the Department of Biology, Gangneung-Wonju National University on the East Sea coast where he was first appointed lecturer (1981) before taking up the position of assistant professor (1983), associate professor (1987) and full professor (1993). In 1985 he had previously completed his Ph.D. dissertation on Korean barnacles at Seoul National University under the supervision of the late Prof. Hoon Soo Kim, a pioneer in marine invertebrate taxonomy and renowned as the father of carcinology in Korea.